Early Attachment to Mothers and Fathers: Contributions to Preschoolers' Emotional Regulation - Fernandes, Carla; Fernandes, Marilia; Santos, António J.; Antunes, Marta; Monteiro, Lígia; Vaughn, Brian E.; Verissimo, Manuela (Frontiers in Psychology, 2021)
Children acquire and develop emotional regulatory skills in the context of parent-child attachment relationships, nonetheless empirical studies have focused mainly on mother and less information is available regarding the role of both parent-child attachment relationships. Furthermore, despite its importance, there is no information regarding preschool years. This study aims to fill this gap by exploring the potential influences of both mother-child and father-child attachments on preschooler’s later emotion regulation observed in the peer group. Attachment Security was assessed at home using the Attachment Behavior Q-set when children were 3 years of age, and emotion regulation was observed in the preschool classrooms attended by the children at age 5, using the California child Q-sort to derive an Emotion Regulation Q-Scale. Results showed that the combined influence of both parent-child attachment security predicted better emotion regulation results, than did the specific contributions of each parent per se. Findings are consistent with integrative approaches that highlight the value of including both mother- and father-child attachment relationships, as well as their combined effect, when studying emotion regulation.